2017
DOI: 10.22632/ccs-2017-252-67
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Data Extraction and Analysis of Left Artifacts on emulated Android Phones: A Case Study of Instant Messaging Applications

Abstract: The fast-growing nature of instant messaging applications usage on Android mobile devices brought about a proportional increase on the number of cyber-attack vectors that could be perpetrated on them. Android mobile phones store significant amount of information in the various memory partitions when Instant Messaging (IM) applications (WhatsApp, Skype, and Facebook) are executed on them. As a result of the enormous crimes committed using instant messaging applications, and the amount of electronic based traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As the author pointed, the objective of introducing SMS feature was to shift away messenger users from their default mobile phone Messages application and see them spend more time in the Messenger application. Derek Walter in Reference 28 claimed that the Messenger application does not save or store any of the SMS in its servers. Indeed, from the experimentation results, it has been shown that it is true that Messenger does not store any SMS in its servers.…”
Section: Comparison With Some Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…As the author pointed, the objective of introducing SMS feature was to shift away messenger users from their default mobile phone Messages application and see them spend more time in the Messenger application. Derek Walter in Reference 28 claimed that the Messenger application does not save or store any of the SMS in its servers. Indeed, from the experimentation results, it has been shown that it is true that Messenger does not store any SMS in its servers.…”
Section: Comparison With Some Related Workmentioning
confidence: 99%
“…Instant messaging software such as Fetion, Skype Messenger, Facebook Instant Messenger, Yahoo Messenger, eBuddy, and WhatsApp Instant Messaging are the most popular and commonly used IM applications. 38,39 A research paper authored by Avis 2 indicated that criminals and violent extremists could use social media applications as a platform for; information exchange, carrying out recruitment and training, planning attacks, conducting fundraising, and spreading of terrorist's propaganda in developing countries. Kenya being a developing country has indeed experienced some occurrences where terrorists have orchestrated their activities through social media applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vast quantity of data can be stored on Android smartphones [2]. The information available on an Android phone encompasses fundamental details, data from various applications, multimedia content, call histories, contact details, images, sent and received messages, as well as the chat applications database like What-sApp database [3]. It is foreseen that artificial intelligence can be used to detect crime-related data among this vast amount of data [4].…”
Section: Introductionmentioning
confidence: 99%
“…Malware attacks on mobile devices have become one of the most dreaded and precarious threats causing economic and information impairments. The study of Ashawa et al 1,2 asserted that the increase and fast‐growing rate at which mobile applications are been used in the 21st century has caused a proportionate growth in the number of cyber‐attacks one of which is malware attacks on mobile and personal computers. Though, malicious applications target different mobile OS platforms, malware targeting Android has become a massive surge recently.…”
Section: Introductionmentioning
confidence: 99%